Long-term impact of tillage on microbial communities of an Eastern European Chernozem - Horia Domnariu; Kristin M. Trippe; Florina Botez; Elena Partal; Carmen Postolache (Scientific Reports)
Abstract As conservation agricultural practices continue to spread, there is a need to understand how reduced tillage impacts soil microbes. Effects of no till (NT) and disk till (DT) relative to moldboard plow (MP) were investigated in a long-term experiment established on Chernozem. Results showed that conservation practices, especially NT, increased total, active and microbial biomass carbon. The effects on diversity measured through amplicon sequencing were greater for prokaryotes than for fungi. NT increased prokaryotic richness at both the lower and the higher taxonomic level, while for both microbial groups it tended to decrease Shannon index at the higher taxonomic level. No differences were observed between DT and MP. Conversely, tillage intensity induced a clear separation of both prokaryotic and fungal communities among all three practices. Comparing abundance of ecologically meaningful groups revealed more abundant saprotrophic fungi in MP and differences in the bacterial groups involved in the N cycle. Differential analysis showed relatively similar numbers of plant growth promoting prokaryotic taxa. However, it also revealed higher numbers of pathogenic fungal taxa that are enriched in NT. Overall, our findings illustrate that tillage changes the structure of both prokaryotic and fungal communities, including distribution of functional groups, without necessarily changing diversity.